Determinant factors of investors’ behavior in investment decision in Indonesian capital markets - Indra Listyarti; Tatik Suryani (Universitas Hayam Wuruk Perbanas, 2014)
This study examines the effect of financial information, macro environment, and subjective norms on investors’ behavior when making investment decisions in Indonesian capital market. It was conducted by a survey design and involved 190 individual investors in three big cities in Indonesia (Jakarta, Surabaya, and Bandung). By using Structural Equation Modeling with Warp-PLS 3.0, the results showed that macro factors had a significantly positive effect on the technical information, the financial information and the macro factors had a significantly positive effect on the investor intentions, and the intentions of investors and the financial information had a significantly positive impact on investment decisions. It was also found that the financial information held a great contribution to build investor intentions and investment decisions. Thus, Indonesian individual investors were rational and sophisticated investors. They were not influenced by the actions of other investors, analyst opinions, and media. The implication of this research was how to provide information comprehensively to investors, which was very important to influence their decisions.